2020
DOI: 10.3390/medicina56050219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Foot Insole for a Down Syndrome Patient with a Flat Foot: A Case Study

Abstract: Background and Objectives: Patients with Down syndrome have many orthopedic problems including flat foot. Insertion of an insole for a flat foot provides support to the medial longitudinal arch; thus, insole therapy is often used to treat a flat foot. However, the influence of an insole insertion on the knee joint kinematics for a patient with Down syndrome is unknown. This study aimed to elucidate the influence of an insole for a flat foot on the knee kinematics during gait for a patient with Down syndrome. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The radiographic studies about the foot structure in DS children with pes planus showed large talo first-metatarsal angle, low navicular height and calcaneal inclination angle in their feet revealing abnormal alignment of the talonavicular and calcaneocuboid joint [5,6].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The radiographic studies about the foot structure in DS children with pes planus showed large talo first-metatarsal angle, low navicular height and calcaneal inclination angle in their feet revealing abnormal alignment of the talonavicular and calcaneocuboid joint [5,6].…”
Section: Introductionmentioning
confidence: 96%
“…The radiographic studies about the foot structure in DS children with pes planus showed large talo first-metatarsal angle, low navicular height and calcaneal inclination angle in their feet revealing abnormal alignment of the talonavicular and calcaneocuboid joint [5,6]. Some studies pointed out that the ligament laxity and hypotonia caused by genetic issue are the main reasons for DS children's pes planus which induce abnormal alignment of foot [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Since flat feet can significantly alter several aspects of the gait pattern of individuals with DS [9], the use of quantitative, computerized gait analysis represents a very useful tool to elucidate the mechanisms with which features related to this genetic condition differentiate the gait of people with DS from unaffected individuals. For example, it has been observed that the flat-footed condition affects the generated power of the ankle, leading to muscle fatigue and an energetically more expensive gait compared with those of individual with DS with a normal arch or healthy subjects [9,10]. However, it is noteworthy that little information is available regarding the trajectory of the Center of Pressure (COP, the point of application of the ground reaction force (GRF)) during the gait of individuals with DS.…”
Section: Introductionmentioning
confidence: 99%
“…This makes children with Down syndrome more susceptible to flat foot which is a plantar ankle condition that does not have an arch. The arch of the plantar ankle works to help support body weight and reduce the load on the plantar ankle (Endo et al, 2020). If the flat foot condition is left unattended, it can cause postural disorders in children when standing or walking (Arumugam et al, 2016).…”
Section: Introductionmentioning
confidence: 99%